2011
DOI: 10.1007/s12192-011-0256-8
|View full text |Cite
|
Sign up to set email alerts
|

Hsp-27 induction requires POU4F2/Brn-3b TF in doxorubicin-treated breast cancer cells, whereas phosphorylation alters its cellular localisation following drug treatment

Abstract: POU4F2/Brn-3b transcription factor (referred to as Brn-3b) is elevated in >60% of breast cancers and profoundly alters growth and behaviour of cancer cells by regulating distinct subsets of target genes. Previous studies showed that Brn-3b was required to maximally transactivate small heat shock protein, HSPB1/Hsp-27 (referred to as , and consequently, Brn-3b expression correlated well with Hsp27 levels in human breast biopsies. In these studies, we showed that Brn-3b is increased in MCF7 breast cancer cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Both Hsp27 and Hsp70 (and other HSPs) can block apoptosis therefore it is complicated to maintain the fine tuning in HSP expression levels to allow the drugs to effectively kill cancer cells. In line with this, Fujita et al (2011) reported in MCF-7 cells that survived to doxorubicin that the POU4F2/Brn-3b transcription factor is increased with concomitant increases in Hsp27 expression. The POU4F2/Brn-3b transcription factor is required to maximally trans -activate Hsp27 and is elevated in >60% of breast cancers altering growth and behavior of cancer cells by regulating distinct subsets of target genes.…”
Section: Introductionsupporting
confidence: 67%
“…Both Hsp27 and Hsp70 (and other HSPs) can block apoptosis therefore it is complicated to maintain the fine tuning in HSP expression levels to allow the drugs to effectively kill cancer cells. In line with this, Fujita et al (2011) reported in MCF-7 cells that survived to doxorubicin that the POU4F2/Brn-3b transcription factor is increased with concomitant increases in Hsp27 expression. The POU4F2/Brn-3b transcription factor is required to maximally trans -activate Hsp27 and is elevated in >60% of breast cancers altering growth and behavior of cancer cells by regulating distinct subsets of target genes.…”
Section: Introductionsupporting
confidence: 67%
“…In breast cancer, POU4F2 can repress BRCA1 expression [36] and interact with estrogen receptor alpha to enhance its activity [35]. POU4F2 can also induce the expression of CCD1 and CDK4 in the context of proliferation and cell cycle progression [34,37], confer migratory and multidrug resistance properties to breast cancer in in vivo models [38], and cooperate with TP53 to increase transcription of pro-apoptotic genes [39]. Importantly, growth factors like the epidermal growth factor (EGF) can stimulate the activity of the POU4F2 promoter and subsequently its mRNA and protein expression, which in turn can affect POU4F2 target genes influencing growth and behavior of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…or higher Electronic supplementary material The online version of this article (doi:10.1007/s12192-015-0662-4) contains supplementary material, which is available to authorized users. eukaryotes (Adamska and Kloppstech 1991;Eisenberg-Domovich et al 1994;Heckathorn et al 1998;Bausero et al 2005;de Miguel et al 2008;Fujita et al 2011). Whether different Hsps interact only with membrane proteins, only with membrane lipids, or with both remains to be explored.…”
Section: Introductionmentioning
confidence: 99%